2020
DOI: 10.3390/molecules25051065
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Absorption of Nanosized lamotrigine Containing Nasal Powder via the Nasal Cavity

Abstract: Nasal drug delivery has become a popular research field in the last years. This is not surprising since the nose possesses unique anatomical and physical properties. Via the nasal mucosa local, systemic, and directly central nerve systemic (CNS) effect is achievable. Powders have favorable physicochemical properties over liquid formulations. Lamotrigine (LAM) is an antiepileptic agent with a relatively mild side effect spectrum, but only available in tablet form on market. Reducing the particle size to the nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Nasal administration offers a non-invasive pathway to delivery drugs for treating both local and systemic diseases, with several advantages of bypassing the blood-brain barrier, avoiding hepatic first-pass elimination, and reducing side effects [ 1 , 2 , 3 ]. Particularly aiming at central nervous system (CNS) diseases, including schizophrenia, migraines, Parkinson’s, etc., intranasal drug delivery via the olfactory and trigeminal routes directly to the brain is capable of providing much more effective drug concentration at lower doses and reduced risk for adverse reactions [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nasal administration offers a non-invasive pathway to delivery drugs for treating both local and systemic diseases, with several advantages of bypassing the blood-brain barrier, avoiding hepatic first-pass elimination, and reducing side effects [ 1 , 2 , 3 ]. Particularly aiming at central nervous system (CNS) diseases, including schizophrenia, migraines, Parkinson’s, etc., intranasal drug delivery via the olfactory and trigeminal routes directly to the brain is capable of providing much more effective drug concentration at lower doses and reduced risk for adverse reactions [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the usage of mucoadhesive additives allows the delivery of nanosized drugs intranasally to overcome the limitations of the particle size requirements for nasal formulations. Based on our previous experience, it can be concluded that the bioavailability of an active pharmaceutical ingredient is increased by decreasing its particle size [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, drug transport to brain across the nasal epithelium could be further improved by using nasal powders (Ambrus et al, 2020;Rassu et al, 2018;Tanaka et al, 2016). The solid particle dissolution and drug release in the fluid lining the nasal epithelium sustain the drug passive diffusion rate, owing to the saturation concentration in contact with the tissue (Colombo et al, 2016;Giuliani et al, 2018;Pozzoli et al, 2017).…”
Section: Introductionmentioning
confidence: 99%